1978
DOI: 10.2343/geochemj.12.29
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of phosphate ions by calcium carbonate.

Abstract: (1) There are some differences in the mode of coprecipitation of phosphate ions with calcium carbonate formed from calcium bicarbonate solution between stirring and non-stirring (keeping still) the solution as follows: The amount of phosphate ions coprecipitated with calcium carbonate is larger when stirred than when kept still. In the keeping still system the amount of phosphate ions coprecipitated with calcite is approximately equal to that with aragonite, whereas in the stirring system the amount increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 27 publications
4
56
0
Order By: Relevance
“…(4) Influence of borate-boron dissolved in a parent solution on the crystal form of precipitat ed calcium carbonate Concerning the co precipitation of anions with calcium carbonate, the present authors have reported the following facts: Fluoride, chloride and phosphate ions are more easily coprecipitated with aragonite than with calcite, although the presence of these anions in a parent solution favors the formation of calcite and inhibits that of aragonite (KITANO, 1962;KITANO and OKUMURA, 1973;KITANO et al, 1975KITANO et al, , 1978. Sulfate ions are more easily coprecipitated with calcite than with aragonite, although the presence of sulfate ions in a parent solution favors the formation of aragonite and inhibits that of calcite (KITANO, 1962;KITANO et al.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…(4) Influence of borate-boron dissolved in a parent solution on the crystal form of precipitat ed calcium carbonate Concerning the co precipitation of anions with calcium carbonate, the present authors have reported the following facts: Fluoride, chloride and phosphate ions are more easily coprecipitated with aragonite than with calcite, although the presence of these anions in a parent solution favors the formation of calcite and inhibits that of aragonite (KITANO, 1962;KITANO and OKUMURA, 1973;KITANO et al, 1975KITANO et al, , 1978. Sulfate ions are more easily coprecipitated with calcite than with aragonite, although the presence of sulfate ions in a parent solution favors the formation of aragonite and inhibits that of calcite (KITANO, 1962;KITANO et al.…”
Section: Discussionmentioning
confidence: 87%
“…UO+ and also anions such as Cl ; F ; S02 ; P03-2 at the separation of calcite and aragonite in water environments (KITANO and KAWASAKI, 1958;KITANO et al, 1968KITANO et al, , 1975KITANO et al, , 1978KITANO and TERAO , 1972;KITANO and OKUMURA, 1973). Very interesting observations were obtained experi mentally for the influence of various anions in a parent solution on the crystal form of forming calcium carbonate and also for the uptake of the anions by forming calcium carbonate.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…The authors have studied the coprecipitation Then, the authors have reexamined the in of cations such as zinc, copper, magnesium, fluence of borate ions in a parent solution on strontium, barium and uranium ions and also of the crystal form of calcium carbonate formed anions such as chloride, fluoride, phosphate, from the solution. borate and sulfate ions (KITANO et al, 1968(KITANO et al, , 1975(KITANO et al, , 1976(KITANO et al, , 1978a(KITANO et al, , 1978bKITANO and EXPERIMENTAL PROCEDURE OOMORI, 1971;KITANO and OKUMURA, 1973). And they have reported the following interest Calcium bicarbonate solution was prepared ing observations: Copper, zinc and magnesium by bubbling calcium carbonate suspension with ions in a parent solution favor aragonite forma carbon dioxide gas.…”
Section: Introductionmentioning
confidence: 99%